Expanding welfare in an age of austerity : increasing protection in an unprotected world - Kevins, Anthony (Amsterdam University Press, 2017)
"In recent decades, the rapid expansion of lower-quality, atypical employment has created a growing group of people excluded not only from generous labor market protections, but from welfare state coverage as well. This situation would seem to call for increased spending on the social safety net, yet governments throughout continental Europe, especially since the financial crisis, have instead been turning to austerity. As a result, they have had to choose between either extending coverage and retrenching the good benefits given to 'insiders' or maintaining the protection, coverage, and benefits of the relatively well-off at the expense of a growing class of excluded 'outsiders'. 'Expanding welfare in an age of austerity: increasing protection in an unprotected world' asks why different nations have taken different approaches in addressing - or not addressing - this problem."--Back cover
Keywords: Blutiger Jupiter -- Musikgruppe -- Europa; Welfare state -- Europe.; État providence -- Europe.; Social welfare and social services.; SOCIAL SCIENCE -- General.; BUSINESS & ECONOMICS -- Economics -- General.; BUSINESS & ECONOMICS -- Reference.; Welfare state; Europe; Wohlfahrtsstaat; Sparpolitik; Social welfare & social services.; dualisation, social policy, benefit access, party politics, public opinion.; Electronic book.